A Note on Variable Prices and Foreign Trade Multipliers - Beckerman, W. (Review of Economic Studies, 1953)
Journal Article A Note on Variable Prices and Foreign Trade Multipliers Get access W. Beckerman W. Beckerman Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 2, 1953, Pages 162–164, https://doi.org/10.2307/2296008 Published: 01 January 1953